PERAN PUSAT ASESMEN PKLK TERHADAP PELAKSANAAN PENDIDIKAN INKLUSIF DI KOTA PADANG - OFI RIEGA (Universitas Negeri Padang, 2015)
Abstract This research be background by Padang city as operator inclusive education city, which one help to be fluent the education’s inclusive then UPT. PK-LK education authorities Padang city shape a new service named Pusat Asesmen PKLK (PAP) Padang city. Function of Pusat Asesmen PKLK are for identify and give right service for children with special need education at inclusive school. This research use descriptive qualitative approach, in focus to role and shape of endorsement from Pusat Asesmen PKLK to be fluent education’s the inclusive at Padang city. Reseach subject are head of PAP, experts, assessors of resource center and parents. Data collection process do through observation, interview and documentation study. The Result of this research show Pusat Asesmen PKLK give endorsement to be fluent education’s inclusive at Padang city, by give recomendation for special children which will go into operator inclusive education school. But servicing are not perfect related less of cooperation problem, less assessors and limited socialization. For the further be expected that Pusat Asesmen PKLK can up grade of cooperation, add the emlpoyee and do more sosialization to society, so that improvement towards education progress for special children can be enhanced. Keywords: inclusive, special children